Perbandingan Sistem Bagi Hasil dalam Ekonomi Syariah dan Praktiknya di Lembaga Keuangan Syariah - Mhd Mashuri Hamdani Lubis; Farhan Rizki Noor Harun; Reni Ria Armayani Hasibuan (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This article discusses the profit-sharing system as one of the main pillars in Islamic economics, focusing on its ideal concept, implementation, challenges, and development opportunities in Islamic financial institutions in Indonesia. This system is based on the principles of justice, partnership, and shared responsibility through mudharabah and musyarakah contracts. Although normatively acknowledged and regulated by Islamic finance fatwas and regulations, its practical application still faces various obstacles such as low Islamic financial literacy, weak supervision, and the dominance of fixed-margin-based products. Nevertheless, digital technology development, the potential of the MSME sector, and the strengthening of Islamic financial regulations and education provide significant opportunities to promote transformation toward a more inclusive and just financial system. Therefore, synergy among financial institutions, regulators, and society is required to optimally realize the implementation of the profit-sharing system in Islamic economic practices.